Myopia as a risk factor for subsequent retinal tears in the course of a symptomatic posterior vitreous detachment - Crim, Nicolás (2017)
Background: Retinal tears complicating the course of a posterior vitreous detachment (PVD) may be unique or multiple, and when multiple they may occur simultaneously or subsequently at different moments in the evolution of a PVD. The purpose of our study was to analyze the prevalence of subsequent retinal tears (SRT) in patients with a PVD, and to identify possible risk factors for SRT. Methods: One hundred and seventy six eyes in 165 consecutive patients that presented one or more retinal tears in the evolution of a symptomatic PVD, with a minimum follow-up of 12 months, were retrospectively evaluated. The primary outcome measure was to characterize the clinical features associated with SRT formation against those eyes with non-subsequent retinal tear (NSRT-retinal tear/s diagnosed at initial examination) formation. For that purpose, this cohort of patients was divided into two different groups: group 1 included eyes presenting one or multiple retinal tears only at initial examination (NSRT), and group 2 eyes that progressed to a further retinal tear/s (SRT) during follow-up. Results: Group 1 comprised 154 eyes from 145 patients, 48.7% males and 51.3% females with a mean age of 56.9 ± 14.0 years (range = 15-89); 17.2% of patients had a previous retinal tear or retinal detachment in the fellow eye; mean number of retinal tears per eye 1.42 ± 0.8 (range = 1-5); 20.8% presented bilateral retinal tears; 59.1% were myopic eyes (p < 0.05). Group 2 comprised 22 eyes from 20 patients; mean age was 53.3 ± 13.6 years (range = 30-69); 63.6% were male (p = 0.13), and 7 patients (31.8%) had a history of SRT or retinal detachment in the fellow eye (p = 0.13). The mean number of retinal tears per eye was 1.36 ± 0.5 (range = 1-2); bilateral retinal tears were noted in 18.2% of eyes; 86.4% were myopic eyes (p = 0.01); 81.8% occurred within a 120 days-period following diagnosis of the first retinal tear. Conclusions: Multiple retinal tears may be diagnosed in the evolution of a PVD. SRT are most frequently observed in myopic patients, and are usually symptomatic. Follow-up must extend for at least 4 months after the initial symptoms.